Editorial Introduction - Suzanne Porath (Networks: An Online Journal for Teacher Research, 2015)
Whether in the PreK-12 classroom or at the college level, action research empowers researchers to observe, reflect and take action on their own practice. In Volume 17, Number1 of Networks: An Online Journal for Teacher Research educators/researchers illustrate how their personal inquiries impacted their practice as pre-service teachers, classroom teachers, or university instructors. The articles in this edition encourage educators to listen to the voices of the students they teach because student voices can teach teachers.